Portrait of the Meaning of Life of Schizophrenia Survivors at Lentera Harmoni Jiwa Foundation (LEMJIWA) Yogyakarta - Wardani, Nurul Annisa; Fahmi Irfanudin (Journal of Islamic Communication and Counseling, 2025)
Each person has a unique meaning of life, shaped by their individual experiences and personal circumstances. Life's meaning can be discovered in various situations, whether in happiness or hardship. This study aims to understand how schizophrenia survivors find meaning in their lives and the processes they undergo to reach this understanding. Using a qualitative method and descriptive approach, data were gathered through observation, interviews, and documentation. The study's findings reveal that, out of three subjects, two have achieved a deep understanding of life's meaning. They exhibit creative values ​​realized through work or enjoyable activities, a positive mindset that helps avoid negativity, and reflective values ​​gained through self-reflection, motivating them to keep growing. On the other hand, one subject remains in the search stage and has not yet fully understood their life's meaning.